The Fluctuation of Aedes Aegypti in Endemic Area of Dengue Hemorrhagic Fever in Surabaya City, Indonesia - Yotopranoto, Subagyo; Kusmartisnawati, Kusmartisnawati; Mulyatno, Kris Cahyo; Arwati, Heny (Indonesian Journal of Tropical and Infectious Disease, 2010)
This research was aimed to describe the density pattern and the fluctuation of Aedes aegypti larval based on the season in dengue haemorrhagic fever (DHF) endemic area in Surabaya city. The population of the research was the house of people together with its breeding sites either inside and outside the house. The 55 houses were randomly chosen in 11 RWs in Nginden Subdistrict. The sample of this research was Aedes aegypti larva obtained from its breeding sites. The sample sizes were all of the larval in the containers existed in the chosen houses. The samples of the larval were taken and carried for identification and documentation of the species. This research was applied in the same houses in January, March, and May 2008 in rainy season. The results indicated that the highest larval index occurred in January with House Index (HI) 76.8%, Container Index (CI) 40.5%, and Breteau Index (BI) 137.5%. There was a decrease in March with HI 63.3%, CI 31.3%, and BI 92.7%. It continued to decrease in May with HI 42.6%, CI 21.1%, and BI 57.4%. All of those larval indices in the three observed months showed a high percentage of larval which was much higher than the safe limit or the critical threshold (5%) as defined by WHO. It implied that people in Nginden Subdistrict were threaten by the infection of DHF. The three indices achieved the peak in January, which was also the peak of the rainy season. It gradually decreased in March and May as the rainy season decreased its intensity of rain. Larval Density Index (LDI) also showed a high value. There were 173 larval/house in January, 187 larval/house in March, and 84.8 larval/house in May. The containers or breeding sites of Aedes were mostly found in January then their existences gradually decreased in March and May. Traditional bath tub was the most productive container inside the house, while drum and bucket were the most productive containers outside the house. Other containers which contributed abundance of larval were refrigerator, flower pot, well, and PDAM meter box.